2013
DOI: 10.1111/obr.12027
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin and incident coronary heart disease and stroke. A systematic review and meta‐analysis of prospective studies

Abstract: The plasma concentration of adiponectin, an adipokine that has anti-inflammatory, anti-atherogenic and insulin sensitizing properties, is lower in obese subjects and could therefore be a target for therapy. In order to review and meta-analyse prospective cohort studies investigating adiponectin concentration and the risk for incident coronary heart disease (CHD) or stroke, a systematic search of MEDLINE, EMBASE and Cochrane databases was performed. Two independent reviewers selected prospective cohort studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
43
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(44 citation statements)
references
References 54 publications
1
43
0
Order By: Relevance
“…This supports the notion that there is only a partial overlap in inflammation-related risk factors for both conditions and that adiponectin has no protective effects against cerebrovascular events. The findings of the SOS cohort on stroke are in line with the majority of previous prospective studies in leaner cohorts that also revealed no association between adiponectin and incidence of stroke after adjustment for confounders (12,30,(36)(37)(38). However, it should be noted that stroke can be ischemic or hemorrhagic, and the type of stroke was not defined in our study.…”
Section: Adiponectin Myocardial Infarction and Strokesupporting
confidence: 75%
See 1 more Smart Citation
“…This supports the notion that there is only a partial overlap in inflammation-related risk factors for both conditions and that adiponectin has no protective effects against cerebrovascular events. The findings of the SOS cohort on stroke are in line with the majority of previous prospective studies in leaner cohorts that also revealed no association between adiponectin and incidence of stroke after adjustment for confounders (12,30,(36)(37)(38). However, it should be noted that stroke can be ischemic or hemorrhagic, and the type of stroke was not defined in our study.…”
Section: Adiponectin Myocardial Infarction and Strokesupporting
confidence: 75%
“…It has been suggested that associations between adiponectin and cardiovascular disease depend on the outcomes that are included in the analysis (25), and this is supported by our data from the SOS Study, which indicate that myocardial infarction and stroke should be analyzed separately. If only studies that have a similar outcome based on fatal and nonfatal myocardial infarction are considered, the direction of association correlates with the stage of cardiovascular disease at study baseline: on the one hand, usually no (26)(27)(28) and, less frequently, inverse (29) associations with risk of myocardial infarction predominate in cohorts that were population based and/or mostly without preexisting cardiovascular disease at baseline (30). On the other hand, positive associations were found mainly (31-33), albeit not exclusively (34), in individuals with a history of cardiovascular disease.…”
Section: Adiponectin Myocardial Infarction and Strokementioning
confidence: 99%
“…In view of this, it is necessary to emphasize that it has been previously demonstrated that MetS had a greater impact on LVH above all in females and its effect was partly independent of the effect of several determinants of LVM [33]. We found that the presence of MetS is able to influence the prevalence of LVH and the increased LVMI, but only in subjects with normal ADPN.…”
Section: Discussionmentioning
confidence: 47%
“…Nevertheless, although numerous subsequent animal studies and in vitro experiments have reported that adiponectin has direct anti-inflammatory, anti-atherogenic, antihypertensive (vasodilatory) and antidiabetic (insulinsensitizing) properties [11][12][13][14], many human studies have failed to show any association between hypoadiponectinaemia and cardiovascular events [15][16][17], and the possibility that a low circulating amount of adiponectin is merely an innocent bystander rather than a genuine risk factor for obesity-related disorders certainly exists.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, numerous animal studies have reported that adiponectin exerts direct anti-inflammatory, anti-atherogenic, antihypertensive (vasodilatory) and antidiabetic (insulinsensitizing) properties [11][12][13][14]. Nevertheless, even though adiponectin has been associated with well-known cardiovascular risk factors [4][5][6][8][9][10], a number of studies have failed to show any association between hypoadiponectinaemia and cardiovascular events in human beings, as summarized in three recent systematic reviews and meta-analyses [15][16][17]. In this context, the results linking adiponectin to hypertension in human beings have also been conflicting [18][19][20][21][22], and a possible direct effect of adiponectin on human resistance arteries has apparently never been tested.…”
mentioning
confidence: 99%